2022
DOI: 10.1111/jfd.13605
|View full text |Cite
|
Sign up to set email alerts
|

Dual resistance to Flavobacterium psychrophilum and Myxobolus cerebralis in rainbow trout (Oncorhynchus mykiss, Walbaum)

Abstract: Flavobacterium psychrophilum, the causative agent of bacterial coldwater disease (BCWD), is found in cultured and wild fishes worldwide and causes significant infection in captive salmonid populations (LaFrentz & Cain, 2004;Starliper, 2011). Mortality associated with infections can be as high as 90% (Barnes & Brown, 2011;Nilsen et al., 2011) depending on water temperature and developmental stage of the host (Decostere et al., 2001;Wood, 1974).Outbreaks causing high mortality can result in massive economic loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Two GR × HAR(75:25) fish had particularly high myxospore loads that, due to the low sample size, could have had a large influence on our comparisons. Yet, other studies have documented similar variability in infection severity of the GR × HAR(75:25) (Schisler et al 2011;Avila et al 2022), and therefore the variability likely reflects real trends. For example, Wagner et al (2012) found that GR × HAR(75:25) and the Ten Sleep Rainbow Trout strain had similar myxospore loads per fish from two different lakes in Utah.…”
Section: Modelmentioning
confidence: 70%
See 1 more Smart Citation
“…Two GR × HAR(75:25) fish had particularly high myxospore loads that, due to the low sample size, could have had a large influence on our comparisons. Yet, other studies have documented similar variability in infection severity of the GR × HAR(75:25) (Schisler et al 2011;Avila et al 2022), and therefore the variability likely reflects real trends. For example, Wagner et al (2012) found that GR × HAR(75:25) and the Ten Sleep Rainbow Trout strain had similar myxospore loads per fish from two different lakes in Utah.…”
Section: Modelmentioning
confidence: 70%
“…2011; Avila et al. 2022), and therefore the variability likely reflects real trends. For example, Wagner et al.…”
Section: Discussionmentioning
confidence: 99%
“…2011, 2012, 2014; Avila et al. 2018, 2022); however, further poststocking studies into long‐term survival, growth, reproduction, and movement of the GR strain in the wild would be beneficial. Additionally, the prevalence and severity of whirling disease as well as the potential negative effects of other pathogens (e.g., Avila et al.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, removal of parasite stages (ciliates, monogenean eggs, digenean larvae, crustacean larvae) by mechanical filtration (Larsen et al ., 2005 ; Heinecke and Buchmann, 2009 ) or biological mussel filtration (Bartsch et al ., 2013 ) has also a potential, although absolute control is not achieved. Another promising strategy is to apply selective breeding of fish with a certain level of natural resistance to infection (Jaafar et al ., 2020 ; Avila et al ., 2022 ). The adaptability of parasites to any environmental disturbance or challenge makes it necessary to combine the different control systems in order to reduce the selective pressure for occurrence of avoidance mechanisms in parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to resist a parasitic infection is genetically determined, which has been indicated for Ichthyophthirius and Myxobolus infections in rainbow trout (Hedrick et al ., 2003 ; Avila et al ., 2022 ). Breeding towards more disease-resistant fish is a possibility, and marker-assisted selective breeding is a tool which has been increasingly used in breeding programmes.…”
Section: Genetic Control Through Breedingmentioning
confidence: 99%